1998
DOI: 10.1562/0031-8655(1998)067<0167:peotsa>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

pH Effects on the Spectroscopic and Photochemical Behavior of Enoxacin: A Steady-State and Time-Resolved Study

Abstract: The spectroscopic and photochemical behavior of Enoxacin (ENX), 1-ethyl-6-fluoro-1,4-dihydro-4-oxo-7-(1-piperazinyl)- 1,8-naphthyridine-3-carboxylic acid, has been investigated in aqueous solutions between pH 3.5 and pH 12. The absorption and emission properties of ENX are strongly affected by pH. The fluorescence quantum yield, 4 x 10(-3) at pH 3.5, increases by a factor of two on going to neutral pH while a strong reduction is observed at alkaline pH. The photodegradation quantum yield also depends on pH, be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
70
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 66 publications
(77 citation statements)
references
References 22 publications
7
70
0
Order By: Relevance
“…[8] Such a transient band is identical to that detected for the same substrate in sulfite buffer (compare Figure 7 in ref. [8] and Figure 1 in ref. [5] ).…”
Section: Evidence Concerning the Course Of The Reactionsupporting
confidence: 76%
See 4 more Smart Citations
“…[8] Such a transient band is identical to that detected for the same substrate in sulfite buffer (compare Figure 7 in ref. [8] and Figure 1 in ref. [5] ).…”
Section: Evidence Concerning the Course Of The Reactionsupporting
confidence: 76%
“…[5,8] With naphthryridinone 1b, we also reported that a different transient band was seen in phosphate buffer (a broad band centred at 670 nm). [8] Such a transient band is identical to that detected for the same substrate in sulfite buffer (compare Figure 7 in ref. [8] and Figure 1 in ref.…”
Section: Evidence Concerning the Course Of The Reactionmentioning
confidence: 51%
See 3 more Smart Citations